Electrical impedance spectroscopy as a potential tool for detecting bone porosity - Ain, Khusnul; Putra, Alfian Pramudita; Rahma, Osmalina Nur; Hikmawati, Dyah; Rahmatillah, Akif; Che Abdullah, Che Azurahanim (Elsevier, 2024)
Electrical measurements of bovine trabecular bone samples revealed a perfect correlation between the electrical and mechanical properties. Electrical parameters have surpassed Broadband Ultrasound Attenuation measurements to predict the mechanical properties of bovine bones. There is a linear relationship between dielectric permittivity and bone mineral density. Studies utilizing electrical impedance spectroscopy to evaluate bone include the characterization and monitoring of titanium bone implants, the characterization of bone tissue, and the monitoring of bone fracture healing progress after osteosynthesis. These studies demonstrate that impedance spectroscopy has outstanding potential for assessing bone quality. This study proposes electrical impedance as a method for characterizing bone porosity. Using the DAQ Analog Discovery as an EIS, two electrodes were utilized to determine bone porosity. The procedures include the EIS scanning process and the analysis of its electrical components using the CPE(RC) circuit model. Five bovine samples were used to demonstrate that the EIS spectrum method can be used to determine bone porosity with a reasonable correlation between the parameters R (R2=0.987, F(1,3)=68.067, p<0.004). and C (R2=0.994, F(1,3)=94.041, p<0.002). While the parameter Q (R2=0.922, F(1,3)=22.568, p<0.018) of CPE can indicate the condition of the bovine cancellous bone scaffold surface.